RISK SITUATION REGULATORES’ PROBLEM IN PEDAGOGICAL RISKOLOGY (Education in the 21st Century, 2023)
Pedagogical riskology is a new scientific branch of pedagogy that, from one hand, examines the behavior of the subjects involved in the educational process, and especially the behavioral aspect of learners and the teacher’s professional and pedagogical activities, on the other hand, pedagogical risk as a socio-economic and psychological phenomenon, as well as the peculiarities of the learners and teacher’s activity in the situation of unavoidable choice.The problem of this study is due to the unpredictability and often-uncontrollable situation of risk in the educational process, which can have a particularly negative impact on the development of the individual of a student. That is why in modern processes the actual problem is the study of risky situations and the disclosure of the features of possible adjustments.Current research and publications related to this problem show that the field of pedagogical riskology is still under development. At the same time, research and scientific work carried out within the framework of general riskology and its other industries; serve as the basis for the expansion and development of research in the field of pedagogical riskology. Thus, such a methodological basis is the theoretical concepts of W. Beckom, N. Luhmann, E. Giddens, A. Mole (U. Beck, N. Luhmann, E. Giddens, A. Mol). These scientists and their followers explain the concept of  "risk", reveal its features, the features of the mechanisms of occurrence and development of risks, classify modern risks and present ways to minimize and eliminate risks and their consequences (real and probable).The purpose of this study is to identify and solve the problem of risk regulators in pedagogical riskology.Novelty: As part of the study, pedagogical approaches to the risk situation are considered, unlike other theories of pedagogical risk, a system of risk regulators has been developed and presented in the pedagogical process.
Keywords: Risk, risk situation, pedagogical process, risk situation regulators, pedagogical risk, personal development